Recent acceleration of biomass burning and carbon losses in Alaskan forests and peatlands - Turetsky, Merritt R.; Kane, Evan S.; Harden, Jennifer W.; Ottmar, Roger D.; Manies, Kristen L.; Hoy, Elizabeth; Kasischke, Eric S. (Nature geoscience, 2011)
Climate change has increased the area affected by forest fires in boreal North America. An analysis of the depth of burning in forests and peatlands in Alaska indicates that ground-layer combustion has accelerated regional carbon losses. Climate change has increased the area affected by forest fires each year in boreal North America 1 , 2 . Increases in burned area and fire frequency are expected to stimulate boreal carbon losses 3 , 4 , 5 . However, the impact of wildfires on carbon emissions is also affected by the severity of burning. How climate change influences the severity of biomass burning has proved difficult to assess. Here, we examined the depth of ground-layer combustion in 178 sites dominated by black spruce in Alaska, using data collected from 31 fire events between 1983 and 2005. We show that the depth of burning increased as the fire season progressed when the annual area burned was small. However, deep burning occurred throughout the fire season when the annual area burned was large. Depth of burning increased late in the fire season in upland forests, but not in peatland and permafrost sites. Simulations of wildfire-induced carbon losses from Alaskan black spruce stands over the past 60 years suggest that ground-layer combustion has accelerated regional carbon losses over the past decade, owing to increases in burn area and late-season burning. As a result, soils in these black spruce stands have become a net source of carbon to the atmosphere, with carbon emissions far exceeding decadal uptake.